Correlated Levels of mRNA and Soma Size in Single Identified Neurons: Evidence for Compartment-specific Regulation of Gene Expression - Ransdell, Joseph L.; Faust, Tyler B.; Schulz, David J. (Frontiers in Molecular Neuroscience, 2010)
In addition to the overall complexity of transcriptional regulation, cells also must take into account the subcellular distribution of these gene products. This is particularly challenging for morphologically complex cells such as neurons. Yet the interaction between cellular morphology and gene expression is poorly understood. Here we provide some of the first evidence for a relationship between neuronal compartment size and maintenance of mRNA levels in neurons. We find that single-cell transcript levels of 18S rRNA, GAPDH, and EF1-alpha, all gene products with primary functions in the cell soma, are strongly correlated to soma size in multiple distinct neuronal types. Levels of mRNA for the K+ channel shal, which is localized exclusively to the soma, are negatively correlated with soma size, suggesting that gene expression does not simply track positively with compartment size. Conversely, levels of beta-actin and beta-tubulin mRNA, which are major cytoskeletal proteins of neuronal processes, do not correlate with soma size, but are strongly correlated with one another. Additionally, actin/tubulin expression levels correlate with voltage-gated ion channels that are uniquely localized to axons. These results suggest that steady-state transcript levels are differentially regulated based on the subcellular compartment within which a given gene product primarily acts.